2014
DOI: 10.1002/cjoc.201300842
|View full text |Cite
|
Sign up to set email alerts
|

Study of Linear and Nonlinear Optical Properties of Four Derivatives of Substituted Aryl Hydrazones of 1,8‐Naphthalimide

Abstract: Four 1,8-naphthalimide hydrazone molecules with different electron-donating groups have been applied in the study of linear and nonlinear optical (NLO) properties. These compounds showed strong green emission in solution.Their NLO properties such as two-photon absorption (TPA) behavior with femtosecond laser pulses ca. 800 nm and excited-state absorption (ESA) behavior with nanosecond laser pulses at 532 nm were investigated. Compound 4 presented the largest two-photon cross section (550 GM) among them due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…These structures are stabilized by aprotic solvents with the sufficiently high dielectric constant (e.g., DMSO, DMF, acetonitrile). This conclusion is consistent with spectral measurements as well as with the theoretical calculations results [22]. The structures A and D C=N charge density is lower than the B and C .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These structures are stabilized by aprotic solvents with the sufficiently high dielectric constant (e.g., DMSO, DMF, acetonitrile). This conclusion is consistent with spectral measurements as well as with the theoretical calculations results [22]. The structures A and D C=N charge density is lower than the B and C .…”
Section: Resultssupporting
confidence: 92%
“…Based on the solvent and the concentration effect on tautomeric equilibrium the lifetime τ 3 was assigned to the hydrazone aggregated forms and τ 1 monomeric form [24]. Similar slightly lower lifetime values for other 1,8-naphthalimide hydrazones were measured in works [22,25].…”
Section: Resultsmentioning
confidence: 75%
“…1,2 In recent years, considerable efforts have been made for the development of more efficient NLO materials; of those, organic conjugated molecules and polymers have emerged as forefront candidates, in addition to more traditional inorganic/semiconductor materials. [3][4][5] The fast response time, large optical nonlinearity, 6 low cost, easy purification and variable molecular design 7 of organic π-conjugated molecules and polymers make them more rele-vant materials in photonic fields such as optical switching, 8,9 optical limiting, 10 tele-communication, 11 signal processing, laser medicine, 12 etc. Generally, the NLO properties of organic materials are determined by their nonlinear absorption (NLA).…”
Section: Introductionmentioning
confidence: 99%
“…Highly conjugated luminogens, such as the naphthalimide (NI) group, are rarely chosen as ideal MC molecules in that they display high fluorescence intensity in dilute solutions, however these intensities will dramatically vanish in the solid state owing to strong π‐π interaction with adjacent molecules. Some reports have shown that 1,8‐naphthalimide hydrazone‐conjugated organic compounds with planar structures and an electron‐donating group, are able to increase fluorescence quantum yields and tune the emission wavelength to longer regions [9] . Stimuli‐responsive dyes with two naphthalimide chromophores have been reported, and offer a good many of intra‐ and intermolecular hydrogen bond interactions and exhibit an apparent mechanochromic fluorescent behavior, which is extremely rare among naphthalimide‐based molecules in the solid state [10] .…”
Section: Introductionmentioning
confidence: 99%